Genetic structure and relationship of three cattle breeds from Rajasthan: Implications for breeding strategies and conservation - B. Prakash,; Deepika, (Journal of Livestock Biodiversity, 2025)
Information on genetic structure and variability of livestock breeds is critical for efficient conservation plans. Here,we present molecular characterization of 3 cattle breeds from Rajasthan state of India on the basis of 21 FAOrecommended microsatellite markers. All the three breeds had high diversity values. The average number of allelesper locus was 9.00 in Tharparkar, 9.76 in Nagori and 10.33 in Kankrej. Gene diversity (expected heterozygosity)was high in all breeds and varied from 0.707 in Tharparkar, 0.713 in Nagori to 0.755 in Kankrej. FIS values were verylow (almost zero) in all the three breeds, with mean FIS values ranging from -0.018 in Kankrej to -0.025 in Nagori.Phylogenetic analysis by Neighbour Joining tree based on Nei’s genetic distance and Cavalli-Sforza Edwards chorddistances generated identical phylogenies, which are in accordance with historical and geographical data.Tharparkar and Kankrej clustered together while Nagori was distinct. AMOVA revealed very low breeddifferentiation among the three breeds. Only 2.19% variation was due to between breed differences and theremaining 97.81% was due to individuals within breeds. PCA and MDS analysis revealed mixed breed structure. Avery high migration (average 11.26 immigrants per generation) was estimated between the three breeds. Thestudy thus reveals very low genetic differentiation despite high genetic variability in the three investigated breeds.